COLAR DE PÉROLAS: A ESTRATÉGIA CHINESA PARA DOMINAR O MAR DO SUL DA CHINA (MSC) E A REGIÃO DO OCEANO ÍNDICO (ROI) - Reis Friede (TRF2, 2019)
The maritime portions of the South China Sea (SCS) and the Indian Ocean Region (IOR) have become of significant importance in the 21st century, as a result of the initially veiled, and now ostensible, global hegemonic ambitions of China, which aims to conquer a global governance space in a new global geopolitical scenario. In this sense, the former conflictual environments, marked by territorial disputes, return to the arena of the "chess game" proper to international relations, replacing the classic ideological clashes that characterized the world context from the second half of the last century on. Although the new conflicts in development are being fought over maritime spaces located in the regions mentioned (SCS and IOR), it is necessary to recognize that the exact point of confrontation will tend to expand to disputes in additional areas, such as Antarctica and the Earth's own georbit, a phenomenon that will inevitably lead, in the geopolitical conjuncture of the current century, to a Second Cold War. For the time being, however, the controversy is restricted to issues related to the Chinese economic and geopolitical interests in the areas mentioned, as well as on the very strategic concept of the so-called "String of Pearls", which is the essence of this article.